MALDI-TOF Mass Spectrometry Fingerprinting Performance Versus 16S rDNA Sequencing to Identify Bacterial Microflora From Seafood Products and Sea Water Samples - Brauge, Thomas; Trigueros, Sylvain; Briet, Arnaud; Debuiche, Sabine; Leleu, Guylaine; Gassilloud, Benoit; Wilhelm, Amandine; Py, Jean-Sébastien; Midelet, Graziella (Frontiers in Marine Science, 2021)
We evaluated the performance of MALDI-TOF MS associated at the Bruker BioTyper™ database for the identification of 713 bacterial strains isolated from seafood products and sea water samples (Anses B3PA collection), under culture conditions that may have been significantly different from those used to create the reference spectrum, versus the 16S rDNA sequencing. We identified 78.8 % of seafood isolates with 46.7 % at species level (Bruker score above 2) and 21.2% (Bruker score between 1.7 and 2) at genus level by the two identification methods except for 3.8% of isolates with a difference of identification between the two methods (Bruker score between 1.7 and 2). There were 41.9 % of isolates (Bruker score below 1.7) with the identification at genus level. We identified 94.4 % of seafood isolates with 16S rDNA sequencing. The MALDI TOF allowed a better strains identification to the species level contrary to the 16s rDNA sequencing which allowed an identification mainly to the genus level. MALDI TOF MS in association with the Bruker database and 16S rDNA sequencing are powerful tools to identify a wide variety of bacteria from seafood but requires further identification by biochemical, molecular technique or other conventional tests.